2020
DOI: 10.18063/ijb.v6i2.265
|View full text |Cite
|
Sign up to set email alerts
|

Combined Porogen Leaching and Emulsion Templating to produce Bone Tissue Engineering Scaffolds

Abstract: Bone has a hierarchy of porosity that is often overlooked when creating tissue engineering scaffolds where pore sizes are typically confined to a single order of magnitude. High internal phase emulsion (HIPE) templating produces polymerized HIPEs (polyHIPEs): highly interconnected porous polymers which have two length scales of porosity covering the 1–100 µm range. However, additional larger scales of porosity cannot be introduced in the standard emulsion formulation. Researchers have previously overcome this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…Casting enables the manufacturing of scaffolds in a wide range of shapes and sizes, depending on the mould design ( Paljevac et al, 2018 ; Diez-Ahedo et al, 2020 ; Dikici et al, 2020a ; Owen et al, 2020 ). Recently, Dikici et al (2020a) reported the fabrication of the PolyHIPEs in tubular form by designing a re-usable tubular silicone mould system that, HIPE can be injected into, polymerised, and recovered easily ( Figure 10Ab ).…”
Section: Development Of the Emulsion Templated Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Casting enables the manufacturing of scaffolds in a wide range of shapes and sizes, depending on the mould design ( Paljevac et al, 2018 ; Diez-Ahedo et al, 2020 ; Dikici et al, 2020a ; Owen et al, 2020 ). Recently, Dikici et al (2020a) reported the fabrication of the PolyHIPEs in tubular form by designing a re-usable tubular silicone mould system that, HIPE can be injected into, polymerised, and recovered easily ( Figure 10Ab ).…”
Section: Development Of the Emulsion Templated Scaffoldsmentioning
confidence: 99%
“…Recently, Dikici et al (2020a) reported the fabrication of the PolyHIPEs in tubular form by designing a re-usable tubular silicone mould system that, HIPE can be injected into, polymerised, and recovered easily ( Figure 10Ab ). Also, sacrificial polymer beads made of PDMS ( Paljevac et al, 2018 ) or alginate ( Owen et al, 2020 ) have been incorporated into emulsion composition prior to polymerisation in a mould to simply introduce multiscale porosity to PolyHIPEs.…”
Section: Development Of the Emulsion Templated Scaffoldsmentioning
confidence: 99%
“…A hydrophilic material is required to create an open surface with W/O emulsions. This can include hydrophilic glass surface[ 78 - 80 ] or alginate[ 81 ].…”
Section: Polyhipe Filter Applicationsmentioning
confidence: 99%
“…Many different materials have been used for bone tissue engineering, ranging from metals and ceramics to natural and synthetic polymers ( Bose et al, 2012 ; Roseti et al, 2017 ; Owen and Reilly, 2018 ). However, of notable recent interest is the development of polymerized high internal phase emulsion (polyHIPE) materials as polymeric scaffolds for bone tissue engineering ( Robinson et al, 2016 ; Lee et al, 2017 ; Paterson et al, 2018 ; Aldemir Dikici et al, 2019 ; Aldemir Dikici and Claeyssens, 2020 ; Owen et al, 2020b ). PolyHIPEs are inherently porous materials that are formed by emulsion templating; the emulsion consists of a curable continuous phase that encapsulates an immiscible internal droplet phase where the internal phase volume exceeds 74%.…”
Section: Introductionmentioning
confidence: 99%